3-Oxo-β-Sultams and 4-Oxo-β-Lactams as chemical tools for activity-based protein profiling of serine hydrolases - Carvalho, Luís Miguel Afonso Ramos de (2021)
Activity-based protein profiling (ABPP) is a technique that analyzes the dynamics in enzymatic activity in complex proteomes by using small molecular probes, deemed activity-based probes (ABPs), containing a reactive group to covalently bind enzyme catalytic residues, a tag for detection of labeled targets and a linker as a spacer and also specificity-enhancing. Different reactive groups have been developed to engage a wide range of enzymatic families but there is a constant need to create new chemical tools to expand the pool of engageable targets. In this work we evaluated two 4-membered ring chemotypes as new reactive groups for ABPP of serine hydrolases. The 3-Oxo-β-Sultam was revealed to be a highly reactive chemotype which labels a wide range of proteins with limited target occupancy. A crystallographic analysis of the reaction of 3-Oxo-β-Sultams with elastase enzymes revealed a previously unknown mechanism of inhibition of these enzymes by sulfonylation, suggesting 3-Oxo-β-Sultam compounds could be used to expand the pool of available sulfonylating tools in chemical biology. 4-Oxo-β-Lactams were shown to potently hit a selected group of serine hydrolase with high target occupancy, including human neutrophil elastase (HNE) and members of the ABHD and DPP families of enzymes. A competitive-ABPP approach revealed high potency of a library of 4-Oxo-β-Lactams to target these enzymes. 4-Oxo-β-Lactams were identified as a new chemotype for DPP8 and DPP9 inhibition. Crystallography experiments revealed a new binding mode of these enzymes with 4-Oxo-β-Lactams, highlighting that these compounds could be used to pursue selective DPP8 or DPP9 inhibitors, a highly pursued field in current medicinal chemistry.